Biodiesel from waste cooking oil in Mexico City. Issue 8 (August 2015) - Sheinbaum, Claudia; Balam, Marco V; Robles, Guillermo; Lelo de Larrea, Sebastian; Mendoza, Roberto
The aim of this article is to evaluate the potential use of biodiesel produced from waste cooking oil in Mexico City. The study is divided in two main areas: the analysis of a waste cooking oil collection pilot project conducted in food markets of a Mexico City region; and the exhaust emissions performance of biodiesel blends measured in buses of the Mexico City public bus transportation network (RTP). Results from the waste cooking oil collection pilot project show that oil quantities disposed depend upon the type of food served and the operational practices in a cuisine establishment. Food markets' waste cooking oil disposal rate from fresh oil is around 10%, but with a very high standard deviation. Emission tests were conducted using the Ride-Along-Vehicle-Emissions-Measuring System in two different types of buses while travelling a regular route. Results shows that the use of biodiesel blends reduces emissions only for buses that have exhaust gas recirculation systems, as analysed by repeated measure analysis of variance. The potential use in Mexico City of waste cooking oil for biodiesel is estimated to cover 2175 buses using a B10 blend.